Pelatihan Aplikasi Pengolah Data untuk Menunjang Percepatan Publikasi Terindeks Scopus dan Web of Science (WoS) - Susanti, Evi; Farida, Nani; Artasasta, Muhammad Ade; Suharti, Suharti; Wijayanti, Chandra; Yuliana, Shinta (Indonesian Journal for Social Responsibility, 2025)
Scientific publications are one of the requirements for student graduation. The importance of scientific publications for students is that they can be used as a portfolio to apply for a job or get a scholarship. However, in publishing an article that is "good science", students still have difficulty analyzing data using several data processing software programs. The purpose of this community service is to provide data processing application training to students to accelerate Scopus and Web of Science (WoS)-indexed publications. The method used was in the form of tiered training attended by 46 students. Data analysis was carried out with a qualitative and quantitative approach using Kirkpatrick's Level 1 and Level 2 evaluation models. The results of this training, in addition to getting a positive satisfaction response from the participants on the training material provided, also gained a fairly good understanding of the training material provided, with a high average task value for each training above 75.